Sites of Acetylation on Newly Synthesized Histone H4 Are Required for Chromatin Assembly and DNA Damage Response Signaling - Ge, Zhongqi (American Society for Microbiology, 2013)
The best-characterized acetylation of newly synthesized histone H4 is the diacetylation of the NH(2)-terminal tail on lysines 5 and 12. Despite its evolutionary conservation, this pattern of modification has not been shown to be essential for either viability or chromatin assembly in any model organism. We demonstrate that mutations in histone H4 lysines 5 and 12 in yeast confer hypersensitivity to replication stress and DNA-damaging agents when combined with mutations in histone H4 lysine 91, which has also been found to be a site of acetylation on soluble histone H4. In addition, these mutations confer a dramatic decrease in cell viability when combined with mutations in histone H3 lysine 56. We also show that mutation of the sites of acetylation on newly synthesized histone H4 results in defects in the reassembly of chromatin structure that accompanies the repair of HO-mediated double-strand breaks. This defect is not due to a decrease in the level of histone H3 lysine 56 acetylation. Intriguingly, mutations that alter the sites of newly synthesized histone H4 acetylation display a marked decrease in levels of phosphorylated H2A (γ-H2AX) in chromatin surrounding the double-strand break. These results indicate that the sites of acetylation on newly synthesized histones H3 and H4 can function in nonoverlapping ways that are required for chromatin assembly, viability, and DNA damage response signaling.